THE IMPACT OF POWERFUL CEOS ON CORPORATE FINANCIAL - Pasila, Topi (My University, 2016)
Nowadays in large publicly listed corporates CEOs have almost a superstar status and the business media has made them even more recognisable for consumers and investors. This leading to that CEOs have even more power over investment decisions, assets and resources in companies. Thus the CEO is also responsible for the financial performance of the company. The purpose of this thesis was to empirically find if a powerful CEO has an impact on the corporate financial performance. Power is seen as a necessary tool to overcome resistance especially in decisionmaking and persuade others in the direction that the CEO desires. This thesis describes CEO power by using chair-duality, tenure length, ownership and termination payment variables. To measure corporate financial performance in companies, this thesis gathered data for ROA, ROE, EPS and P/B ratio. All the data has been gathered from companies that are listed in the S&P 500 index during the years of 2010-2014. This thesis combines and analyses the data with ttest and linear regression to empirically examine the relations with CEO power and financial performance. Also correlations between the CEO power variables are examined. The results showed that the power of the CEO has both negative and positive impacts on the financial performance of the company. Termination payment showed a negative effect on all of the performance variables except ROE, suggesting strongly that it is the most significant power variable. Other CEO power variables have either positive, negative or non significant effects on the financial performance. Ownership and chair-duality have both positive and negative effects on the corporate performance. These findings are in line with earlier studies, as these studies also showed varied results. To conclude there is no clear pattern which of these CEO power variables effect financial performance most significantly, except termination payment.
Keywords: CEO; poerful; corporate; performance; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|